A phase I study of romidepsin, gemcitabine, dexamethasone and cisplatin combination therapy in the treatment of peripheral T-cell and diffuse large B-cell lymphoma; the Canadian cancer trials group LY.15 study†. Issue 4 (21st March 2019) - Reiman, Tony; Savage, Kerry J.; Crump, Michael; Cheung, Matthew C.; MacDonald, David; Buckstein, Rena; Couban, Stephen; Piliotis, Eugenia; Imrie, Kevin; Spaner, David; Shivakumar, Sudeep; Kuruvilla, John; et al.
Abstract: We investigated GDP (gemcitabine, 1000 mg/m 2 IV d1, d8; dexamethasone, 40 mg po d1-4; cisplatin, 75 mg/m 2 IV d1) combined with romidepsin on days 1 and 8 every 21 days to a maximum of six cycles in a standard 3 + 3, phase I dose escalation trial for patients with relapsed/refractory peripheral T-cell (PTCL) or diffuse large B-cell (DLBCL) lymphoma (NCT01846390). After treating four patients, gemcitabine and romidepsin were given on days 1 and 15 every 28 days. On the 21-day schedule at 6 mg/m 2 romidepsin, there were three dose-limiting toxicities (DLTs) among four patients. On the 28-day schedule, there were no DLTs at the 6, 8, or 10 mg/m 2 dose. At 12 mg/m 2, there were four observed grade 3 DLTs among six evaluable patients. Full doses of GDP can be combined with a recommended phase II romidepsin dose of 10 mg/m 2 if given on a day 1, 15 every 28 days schedule.